Olive Mill Wastewater Valorization in Multifunctional Biopolymer Composites for Antibacterial Packaging Application - Sisti, Laura (Int J Mol Sci, 2019)
Olive mill wastewater (OMW) is the aqueous waste derived from the production of virgin olive oil. OMW typically contains a wide range of phenol-type molecules, which are natural antioxidants and/or antibacterials. In order to exploit the bioactive molecules and simultaneously decrease the environmental impact of such a food waste stream, OMW has been intercalated into the host structure of ZnAl layered double hydroxide (LDH) and employed as an integrative filler for the preparation of poly(butylene succinate) (PBS) composites by in situ polymerization. From the view point of the polymer continuous phase as well as from the side of the hybrid filler, an investigation was performed in terms of molecular and morphological characteristics by gel permeation chromatography (GPC) and X-ray diffraction (XRD); also, the thermal and mechanical properties were evaluated by thermogravimetric analysis (TGA), differential scanning calorimetry (DSC), and dynamic thermomechanical analysis (DMTA). Antibacterial properties have been assessed against a Gram-positive and a Gram-negative bacterium, Staphylococcus aureus and Escherichia coli, respectively, as representatives of potential agents of foodborne illnesses.